1982
DOI: 10.1037/0021-843x.91.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Differential hypnotic responsivity of smokers, phobics, chronic-pain control patients: A failure to confirm.

Abstract: The recent claims that hypnotic responsivity may be related to such presenting symptomatology as phobias or chronic pain were examined. A retrospective analysis comparing the differential responsivity of a consecutive patient series (N = 386) on the Hypnotic Induction Profile (HIP) and the Tellegen Absorption Scale (TAS) was carried out. Patients were categorized as phobics (n = 95), smokers (n = 226), and chronic-pain sufferers-(n = 65). Phobic patients were also subclassified as monophobic (n = 54) or polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Three studies (Frischholz, Spiegel, Spiegel, Balma, & Markell, 1982; D. Spiegel, Frischholz, Maruffi, & Spiegel, 1981;Owens, Bliss, Koester, & Jeppsen, 1990) found phobics not to be higher in hypnotizability than the general population or other psychiatric groups. D. Spiegel et al (1981) found no such relationship in a group of flying phobics, an environmentally based phobia, and concluded that a major confound of previous studies was a lack of control for age differences between phobia and comparison groups.…”
Section: Relationships Between Hypnotizability and Phobia Presencementioning
confidence: 99%
“…Three studies (Frischholz, Spiegel, Spiegel, Balma, & Markell, 1982; D. Spiegel, Frischholz, Maruffi, & Spiegel, 1981;Owens, Bliss, Koester, & Jeppsen, 1990) found phobics not to be higher in hypnotizability than the general population or other psychiatric groups. D. Spiegel et al (1981) found no such relationship in a group of flying phobics, an environmentally based phobia, and concluded that a major confound of previous studies was a lack of control for age differences between phobia and comparison groups.…”
Section: Relationships Between Hypnotizability and Phobia Presencementioning
confidence: 99%
“…The present study is the fourth one to find a relationship between hypnotizability and phobic behavior using comparable measures of susceptibility. The discrepancy between the findings of these four studies and those of Frischholz et al (1982) may reflect differences in the measurement properties of the HIP and standard measures of hypnotizability and/or age differences in the various samples examined. Future research on this topic needs to take susceptibility measurement and potential age confounds into account.…”
Section: Discussionmentioning
confidence: 73%
“…The age factor. The mean ages for the phobic and normative samples were considerably lower than for the three samples reported by Frischholz et al (1982). The phobic subjects ranged in age from 21 to 59 years (M = 30.6), whereas for the normative sample the age range was from 18 to 2 All 54 patients were also prescreened on the Fear Survey Schedule (FSS; Wolpe & Lang, 1964).…”
Section: Susceptibility Comparisonsmentioning
confidence: 89%
See 1 more Smart Citation
“…in a study of patients with dental phobic illness, reported a significantly higher mean hypnotizability rating in their group than in the normal population, thus supporting our findings. Frischholz et al (1982) failed to confirm a correlation between phobic behavior and high hypnotizability. This might be explained by their use of an entirely different technique to measure hypnotizability.…”
Section: The Relevance Of Laboratory Scales To Clinical Eventsmentioning
confidence: 95%